Assessment of the Correlation of rs7920721 in the ECHDC3 Gene with Alzheimer's Disease in the Iranian Population - Zahra Kalantari; Elham Siasi; kumarss amini (Journal of Sciences, Islamic Republic of Iran)
Alzheimer's disease is the most common cause of dementia in the elderly. One of the polymorphisms in Alzheimer's disease is rs7920721 in the ECHDC3 gene, which has not been studied in the population of Iranian Alzheimer's patients and was evaluated in the present study. In 2021, 100 patients with Alzheimer's disease and 100 healthy controls performed the current case-control analysis. Following blood sampling and DNA extraction, rs7920721 polymorphism was examined using Tetra ARMS PCR. The frequency of AA, AG and GG genotypes in rs7920721 in the control group was 89, 10, and 1%, respectively; in people with Alzheimer's disease, they were 73, 23, and 4%, respectively (P = 0.014). The frequency of A and G alleles in the control group was 94% and 6%, respectively, and in people with Alzheimer's disease, they were 84.5% and 15.5%, respectively (P = 0.046). The value (OR = 2.874) (CI 95% = 1.43-5.77) indicated an increased probability of disease in the presence of polymorphism. Both the case and control populations were also in the Hardy-Weinberg equilibrium. The results of the present study showed that the presence of the G allele in rs7920721 of the ECHDC3 gene could be associated with an increased risk of Alzheimer's disease in the Iranian population. As a result, this polymorphism can be introduced as a potential biomarker for Alzheimer's disease.